“The Real Deal”: Managing Intimacy Within Friendship at a Distance - Policarpo, Verónica (Qualitative Sociology Review, 2016)
How is intimacy constructed between friends who live apart, at a long distance? Family studies have paid considerable attention to the (re)negotiation processes of personal and intimate bonds within transnational families. However, less attention has been paid to the ways in which these structural constraints affect intimate relationships between friends. As significant members of the personal networks of individuals, friends have a supportive role that, in the continuum of other personal relationships (family, co-workers, neighbors, acquaintances), is challenged by the increasing mobility that characterizes contemporary global post-industrial societies. While a significant amount of literature has underlined the negative impact of geographical distance in friendships, other studies have suggested otherwise, stressing the renewed importance of friendship ties between geographically long-distant young adults. This paper explores long distance friendships (LDFs) focusing mainly on two dimensions: the meanings given to intimacy and the practices of friendship at a distance. The main hypothesis is that transformations of intimacy between long-distant friends are likely to be associated with reconfiguration of the meanings given to friendship, as well as to the norms that regulate them. On the one hand, the erosion of friendship is associated with the impossibility of keeping a face-to-face, co-present, accompanying contact, which is part of the expected normative role of friendship. On the other hand, its reconfiguration is mostly associated with those routines and rituals that keep friendship alive by permanently reenacting a sense of self identity and “ontological security” through the “work of memory.” The role of information and communication technologies (ICT) in fostering intimacy within an LDF is also explored, as these have considerably changed the ways we relate to geographical distance and, therefore, the norms that shape intimate relationships.